Principles in Elementary School Curriculum Development - Nia Pratiwi Hasan; Oktavian Ali; Febrianti Tangahu; Sri Dianita Ngau; Istianti Bulla; Desi frestiawaty Lukman; Ida Fauziah S. Lakoro; Putri Sandika Yusuf; Moh Arif; Marsella Desriyarini Gui (International Journal of Advanced Technology and Social Sciences, 2023)
This research focus to investigates the key principles of the development curriculum in elementary school (SD). The factors such as relevance, holistic, participatory, and conformity with educational stardads are the main focus in designing an effective curriculum. Furthermore, the reaserch also highlighta the flexibility, interconnectedness between the subjects, and  problem - solving orientation as  crucial elements in developing a curriculum that is responsive to student needs. Moreover, active learning approaches, formative and summative assessments, and the use of educational technology are integrated to ensure a comprehensive learning experience. The research objective is to make a contribution to the development of an elementary school curriculum that is more adaptive and supports student's comprehensive development